(untitled) (Texas Journal of Medical Science, 2023)
Knowledge of occupational safety and health is very important for every job, but in practice there are still violations of OHS committed by Repairman such as not using personal protective equipment which is a mandatory requirement to carry out when doing work. By not implementing the OHS program in the workshop, it will have a negative impact in the form of increased incidence of work accidents and occupational diseases. Hazard and Operability Study (HAZOPS) is an attempt to identify the hazards of a process if it deviates from what it should be, hazops is a very systematic, thorough, and complete technique. Based on the results of preliminary studies that have been carried out, it is found that Griya Motor 168 City Market South Tangerang has 6 workers, all workers do not use personal protective equipment, for this reason researchers are interested in examining risks using the HAZOPS method . The general purpose of this research is to analyze occupational safety and health risks using the Hazard and Operability Study (HAZOPS) method at the Griya Motor 168 Pondok Cabe Workshop in South Tangerang. This research is a qualitative research. The techniques used in data collection are field observations and interviews. Data analysis begins with identifying Occupational Safety and Health risks by determining study points (nodes), deviations, causes, consequences and actions. Based on the results of the study, 8 potential hazards were obtained with 2 high categories, 4 medium categories, and 2 low categories. With this research, it is hoped that the company will improve safety for workers to reduce the risk of work accidents, for PPE, it should be emphasized and controlled because there are still workers who are negligent in using PPE